Regulation and Mechanism of Phosphoribosylpyrophosphate Synthetase: Repression by End Products - White, Mary N. (J Bacteriol, 1971)
Phosphoribosylpyrophosphate (PRPP) synthetase participates in the biosynthesis in bacteria of purine nucleotides, pyrimidine nucleotides, tryptophan, and histidine. The regulation of the synthesis of PRPP synthetase in Salmonella typhimurium was studied. Addition of end products to the growth medium, singly or in combination, resulted in small decreases in the specific activity of PRPP synthetase, but levels of the enzyme were never decreased to less than half of those found when the bacteria were grown on minimal medium. Growth of the bacteria on several different carbon sources or starvation for phosphate had little effect on the specific activity of PRPP synthetase. Over-production of histidine in a histidine regulatory mutant, which would be expected to result in a depletion of intracellular PRPP pools, did not alter PRPP synthetase specific activity. PRPP synthetase levels were examined in auxotrophic strains of S. typhimurium that had been starved for the end products of PRPP. In each case derepression of an enzyme in the biosynthetic pathway for the limiting end product was demonstrated. However, only alterations in the levels of pyrimidine bases in the culture medium brought about derepression and repression of PRPP synthetase. Excess pyrimidines do not completely repress the enzyme. Deprivation of exponentially growing cells for pyrimidines by growth of an auxotrophic mutant on media containing orotic acid, which enters the cells slowly, resulted in a 10-fold derepression of PRPP synthetase. Derepression of PRPP synthetase during uracil starvation was prevented by chloramphenicol. The PRPP synthetase activities of extracts from repressed and derepressed cells responded in identical fashion to heat inactivation, cellulose acetate electrophoresis at several pH values, and in kinetic experiments.